Web Technologies and the Integration of Different E-Learning Strategies in Education - Cartelli, Antonio (International Journal of Web-Based Learning and Teaching Technologies, 2008)
The article aims at presenting some experiences concerning new ways of introducing ICT in teaching and especially the use of Web technologies in education. It starts with the analysis of the results that the author obtained with little groups of students, while using special Web sites (i.e., online information systems) for the collection of bibliographies and for the management of data on ancient manuscripts. The observation of the features of the communities (both of learners and of practice) for those classes, led him to hypothesize that information systems could induce the creation of communities where never seen before and new ways of teaching could be introduced in education. Subsequently, the structure of the information system TETIS and its use in a master course for teachers are reported. It is evidenced, among other things, how that system (born for making transparent teaching processes and implementing teachers’ practices) was used together with a traditional e-learning platform for the management of the master course.At last, some introductory results obtained from the use of the TETIS platform are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9qd2x0dC4yMDA4MDQwMTAy